1997
DOI: 10.1055/s-0038-1657708
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Thrombomodulin Gene Mutation in a Patient Suffering from Sagittal Sinus Thrombosis

Abstract: SummaryThrombomodulin is an endothelial cell membrane glycoprotein that promotes protein C activation. It has been clearly demonstrated that the anticoagulant functions of the protein C system are important in the prevention of thromboembolic disease. Patients with protein C or protein S deficiency and/or resistance to activated protein C (APC resistance) are at higher risk for developing thromboembolic disease. The first mutation in the thrombomodulin gene was discovered in an American patient suffering from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…The substitution Ala25Thr (mutation G127A) was identified in a screening program of patients with MI. 20,24 The same mutation has been identified in a patient with venous thrombophilia 19 and in one patient with both venous and arterial thrombosis. 29 Point mutations leading to substitutions Gly61Ala (G236C), Arg385Ser (G1209T), Asp468Tyr (G1456T), Pro477Ser (C1483T), Pro483Leu (C1502T) and to the premature STOP306 (del791-801) have been identified in screening programs involving patients with venous thrombophilia.…”
Section: Mutations Investigatedmentioning
confidence: 66%
See 2 more Smart Citations
“…The substitution Ala25Thr (mutation G127A) was identified in a screening program of patients with MI. 20,24 The same mutation has been identified in a patient with venous thrombophilia 19 and in one patient with both venous and arterial thrombosis. 29 Point mutations leading to substitutions Gly61Ala (G236C), Arg385Ser (G1209T), Asp468Tyr (G1456T), Pro477Ser (C1483T), Pro483Leu (C1502T) and to the premature STOP306 (del791-801) have been identified in screening programs involving patients with venous thrombophilia.…”
Section: Mutations Investigatedmentioning
confidence: 66%
“…The lack of any identified functional defect with this mutant is compatible with inconsistent relationships between mutation, thromboembolic disease, and plasma levels of soluble TM. [16][17][18][19] This work has demonstrated that certain mutations of the TM gene may have a detrimental effect on the expression and protein C activation cofactor function of the protein. These results suggest a plausible mechanism by which TM gene mutations might influence venous and arterial thrombotic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APC, in conjunction with its cofactor protein S, degrades factors Va and VIIIa on the phospholipid surface, thereby attenuating the coagulation cascade. Defects in the protein C anticoagulant pathway have been implicated as the underlying risk factors for the development of venous and arterial thrombosis (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Therefore, a hereditary deficiency of thrombomodulin may very well play a role as a risk factor for thrombotic disease. A number of missense mutations are currently known in the thrombomodulin gene (THMD) of patients with venous thrombosis (Norlund et al, 1997). A particular aminoacid dimorphism, Ala 455 Val, was found with frequencies of 0.81/0.18 in Caucasian patients who suffered from thrombophilia (van der Velden et al, 1991).…”
Section: Thrombomodulin Thmd Ala455valmentioning
confidence: 99%